The Stigma of Being "Haitian" in The Bahamas - Fielding, William J.; Ballance, Virginia; Scriven, Carol; McDonald, Thaddeus; Johnson, Pandora (International Journal of Bahamian Studies, 2008)
Haitian nationals have been migrating to and settling in The Bahamas for hundreds of years. However the presence of Haitians in The Bahamas has been an ever-increasing cause for concern. In 1963 the Haitian community accounted for 3.2% of the population; in 2000 it represented 7.1% and was numerically the largest migrant group in The Bahamas. The relatively high numbers of Haitian migrants on some Bahamian islands have raised fears that The Bahamas is being overwhelmed by this group; in some enumeration districts Haitian nationals account for more than 20% of the population. In common with migrant groups elsewhere, a stigma has become attached to being a Haitian migrant in the Bahamas.Primarily through the use of census data and newspaper articles, this paper attempts to explain this stigma. Haitian migrants are associated with illegal status, poor education, and poverty. Language is a barrier which prevents Haitian migrants from fully participating in society and makes them distinct from the general population. First-generation migrants may face the prospect of being state-less. The paper stresses the need for the resident community to ensure that the stigma does not result in marginalization and lead to a breakdown in relations between the Haitian and non-Haitian groups.